Analisis Komparasi Laju Pertumbuhan dan Kontribusi Pajak Daerah terhadap Pendapatan Asli Daerah di Kota Pangkalpinang dan Kabupaten Belitung - Mastira, Ovina; Zukhri, Nizwan; Saputra, Darman (Journal of Political Issues, 2020)
Local governments have the authority and obligation to implement regional autonomy more independently to reduce the level of fiscal dependence on the central goverment. One way is to maximize the recepit of PAD, one of which is local tax. The purpose of the study was to analyze the growth rate and contribution of entertainment taxes, hotel taxes and advertisement taxes on PAD in the Bangka Belitung Islands Province. The analysis used in this research is quantitative descriptive analysis, namely by collecting, compiling and calculating data in the form of reports on the realization of financial budgets in the Pangkalpinang City and Belitung Regency by using the ratio of the growth rate and contribution ratio. The results showed that the PAD of Belitung Regency was better than City of Pangkalpinang. The growth rate of entertainment tax in Pangkalpinang City lower than Belitung Regency with both categories unsuccessful, but the contribution given by entertainment tax in Pangkalpinang City is higer than Belitung Regency with the category of both being very lacking. The growth rate and contribution of hotel tax in Pangkalpinang City is lower than Belitung Regency with the category of hotel tax growth rate in Pangkalpinang City unsuccessful while Belitung Regency is less, while the hotel tax contribution is both very lacking. The growth rate and the contribution of advertisement tax in Pangkalpinang City is higer than Belitung Regency with the category of the advertisement tax growth rate, both of them are not successful while the contributions given by advertisement tax are bot very lacking.